New perspectives on service teaching : tapping into the student experience. - Kirkup, Les (Australian Learning and Teaching Council, 2009)
Report from a research study that aimed to develop an effective approach to the curriculum development of physics subjects designed for non-physics majors in order to enhance student engagement and learning, and which is sensitive to the future needs of students. This was accomplished by directly tapping into the student experience of the undergraduate curriculum, for example, by attendance at lectures and laboratories in the 'serviced' disciplines, as well as through surveys, interviews and reviewing course materials available to students in an online environment. The study focused on a large enrolment first year physics service subject at the University of Technology, Sydney, allowing approaches to examining the student experience to be evaluated, as well the trialling of innovations designed to enhance that experience. [Executive summary, ed]